PENERAPAN PEMBELAJARAN DIFERENSIASI PADA KEGIATAN EVALUASI PENDIDIKAN PANCASILA DI KELAS 5A SD NEGERI BENDUNGAN SEMARANG - Tri Muliani; Salasil Haqqillah; Nur Indah Wahyuni; Luthfaida Mayasari (STKIP Subang, 2023)
Differentiated learning is the implementation of learning in which the teacher provides action to different students according to their needs. The main goal of differentiated learning is to ensure that each student can reach their maximum potential and feel motivated in the learning process. One example of technologybased evaluation media that can be applied in evaluating elementary school students is Quizizz Paper Mode. Quizizz Paper Mode is an application used to evaluate technology-based learning in the form of interactive quizzes conducted face-to-face. In practice, students answer quizzes given by the teacher by lifting the Q Cards sheet that has been distributed and the teacher will scan the student's answers with the scanner in the account. Quizizz on smartphones. The aim of this research is to apply differentiation learning in evaluation activities for Pancasila Education subjects in class 5A at Bandungan Elementary School, Semarang. This research uses qualitative methods by directly practicing differentiated learning and introducing the use of Quizizz Paper Mode to class 5A students at SD Negeri Bendungan Semarang as a formative evaluation. The results of this research are that quiziz papermode is effectively used to evaluate Pancasila Education at Bendungan State Elementary School.